Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan CV. Widya Pustaka Kabupaten Tasikmalaya - Alya Putri Salsabila; Rita Tri Yusnita; Ai Kusmiati Asyiah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The purpose of this study is to determine and analyze the effect of reward and punishment on the performance of employees at CV. Widya Pustaka, Tasikmalaya Regency. The research method used is descriptive method with a quantitative approach to 31 respondents who are employees of CV. Widya Pustaka, Tasikmalaya Regency. The types of data used are primary data and secondary data. The data analysis method used in this study is multiple linear regression analysis. The test results prove that reward and punishment have a positive and significant effect simultaneously or partially on the performance of CV employees Widya Pustaka, Tasikmalaya Regency.